High-speed Impact Drop Tower Tests of Cylindrical Granular Ice Specimens - Böhm, Angelo; Müller, Franciska; Herrnring, Hauke; von Bock und Polach, Rüdiger Ulrich Franz (POAC, 2023)
Global warming might increase the marginal ice zone, and it increases the accessibility of the Northern Sea Route and the Northwest Passage for the shipping industry, which reduces the shipping time and fuel consumption in comparison to the Suez Canal Route on single voyages. Thus it is presumed that global warming will enlarge the area of possible propeller-ice and wave-ice structure interactions with ships and structures of lower ice classes or less ice strengthening. The interaction velocities between ice and marine structures are often relatively slow, but some scenarios have high relative interaction velocities, such as in propeller-ice interactions. However, experimental data and knowledge on the mechanical behavior in the high-velocity range of ice are scarce. This paper describes high-speed impact drop tower tests of cylindrical granular ice specimens, where adjusting the initial drop height can regulate the impact energy level. Depending on the prevailing conditions, sea ice growth can result in several different grain structures. This study utilizes granular fresh water ice, which allows consistency and repeatability of the mechanical behavior and results in conservatively (high) measured compressive strength values compared to saline sea ice. Two test cases are shown and analyzed. In the first case, the hammer impacts the ice specimen positioned on the measuring platform. In the second case, the specimen is also positioned on the measuring platform, but rubber plates are placed between the hammer, the ice specimen, and the measuring platform. All test cases are conducted at three different impact velocities. Force-displacement curves are shown besides high-speed recordings to distinguish between failure modes, and the influence of the end-cap conditions by using rubber plates is discussed. In addition, the paper compares the data from drop tower tests to conventional ice compression tests. This study highlights the impact of boundary conditions and seeks to contribute to developing numerical ice ...